Balloon-mounted stents for acute intracranial large vessel occlusion secondary to presumed atherosclerotic disease: evolution in an era of supple intermediate catheters. (15th May 2019) - Gross, Bradley A; Desai, Shashvat M; Walker, Gregory; Jankowitz, Brian Thomas; Jadhav, Ashutosh; Jovin, Tudor G
Abstract : Introduction: Treatment of acute large vessel occlusion (LVO) stroke secondary to intracranial atherosclerotic disease (ICAD) is more nuanced with disparate and infrequently reported outcomes. The deployment of balloon-mounted stents presents an expedient approach with renewed feasibility in the modern era of supple intermediate catheters. Methods: A prospectively maintained endovascular stroke database was searched for patients undergoing intracranial stenting with balloon-mounted stents for acute LVO. Demographic, angiographic, and clinical data were extracted to determine procedural technique and success, measured both angiographically and clinically. Results: Sixty patients underwent stenting for acute LVO secondary to ICAD. Mean presenting National Institutes of Health Stroke Scale (NIHSS) score was 18 and 62% of treated sites were in the posterior circulation. Cases were performed under IV conscious sedation unless the patient was already intubated. Successful recanalization was achieved in 93% of cases (Thrombolysis in Cerebral Infarction (TICI) grade 2b in 48% and TICI grade 3 in 45%). Mean improvement in NIHSS score on post-procedure day 1 was 3.4. Good outcome (modified Rankin Scale score 0–2) at 3 months was 34% and the mortality rate was 34%. The rate of peri-procedural symptomatic hemorrhage was 8% and the rate of acute/subacute stent thrombosis was 7%. In this small cohort, patient age, sex, presenting NIHSS, comorbidities, smoking, tissue plasminogen activator administration, and stent location were not significant predictors of recanalization or good outcome. Conclusion: Treatment of acute LVO stroke with balloon-mounted stents for ICAD has reperfusion rates and clinical outcomes comparable to thrombectomy, with higher rates of hemorrhage and mortality. Because stent placement was performed after attempted thrombectomy, a trial of primary stenting versus thrombectomy should be considered in patients suspected of underlying ICAD.